Genotype-environment interactions on growth and inner shell color variation in Hyriopsis cumingii cultured in different iron-level substrates - Xuefeng Lv; Zhiyan Wang; Quanzhi Bao; Changzhi Li; Tingting Lu; Yuyang Wu; Chuntong Liu; Zhiyi Bai (Aquaculture Reports)
Hyriopsis cumingii is a species that naturally inhabits substrates rich in various metal elements. Iron, essential for several biological processes, significantly influences the growth and development of bivalves. This study established nine full-sibling families and conducted an 11-month cultivation experiment involving five different levels of iron content in substrates (1.75 %, 3.85 %, 4.75 %, 5.95 %, and 6.85 %) to investigate the impact of varying iron concentrations on the growth and inner shell color of H. cumingii. The findings revealed that H. cumingii demonstrated significantly enhanced growth under the Iron 3 condition (4.75 %), while individuals cultivated under Iron 4 (5.95 %) exhibited a deeper purple pigmentation in their inner shell. Heritability estimates for growth and inner shell color traits ranged from 0.07 to 0.25 across the experimental population. The anal angle radial rib length (AARRL) displayed stronger genetic and phenotypic correlations with body weight (BW) and shell width (SW) compared to shell height (SH) and total shell height (TSH). Notably, significant gene-environment interaction effects (G × E) were notably observed for the color exhibited by the inner shell and growth-related traits, especially between Iron 1 and Iron 3, as well as between Iron 3 and Iron 5. The comprehensive estimation of breeding values showed that Family 7 exhibited superior performance across all traits under different conditions, positioning it as a promising candidate for genetic improvement. This research underscores the considerable influence of iron concentrations in substrates on the growth and shell coloration of H. cumingii, offering valuable insights for developing selective breeding strategies.